Controlled skyrmion ratchet in linear protrusion defects - Souza, J. C. Bellizotti [UNESP]; Vizarim, N. P. [UNESP]; Reichhardt, C. J. O.; Reichhardt, C.; Venegas, P. A. [UNESP] (American Physical Society (APS), 2024)
Using atomistic simulations, we investigate the dynamical behavior of a single skyrmion interacting with an asymmetric linear protrusion array under external ac driving. The linear protrusion array is placed in the xy plane and is composed of magnetic walls near the edge of the nanotrack that have angled linear protrusions into the nanotrack. The structure forms a hard axis for −x direction motion and an easy axis for +x direction motion. When the ac drive is applied along the x direction, the skyrmion moves along the hard direction of the substrate asymmetry in three phases: a pinned phase with localized skyrmion orbits, a constant velocity phase where the orbits become delocalized, and a reentrant pinned phase with larger localized orbits. We measure the dependence of the skyrmion velocity on the frequency and amplitude of the ac drive. All three phases appear for all frequency values simulated here, and in the constant velocity phase the skyrmion velocity depends only on the frequency and not on the amplitude of the ac drive. When ac driving is applied in the y direction, the skyrmion moves along the easy direction of the substrate asymmetry and exhibits the same three phases as for x-direction driving along with a fourth phase which, at high driving frequencies, consists of a series of constant velocity phases, each with different average skyrmion velocities. For low frequencies, the constant velocity phase is lost and the skyrmion speed increases linearly with increasing ac drive amplitude due to a Magnus boost effect. Our findings suggest new ways to create reliable data transport for spintronic devices using skyrmions as information carriers, where the skyrmion direction and speed can be controlled by varying only the ac drive amplitude and frequency.